(untitled) (Palíndromo, 2025)
This article investigates the challenges and possibilities of teaching visual arts in connection with museums and exhibition spaces, from the perspective of Brazilian heritage education and the impacts of the platformization of education in the state of Paraná. The analysis starts from the recognition of inequalities in access to culture and the systematic absence of Brazilian cultural heritage in the school curriculum, revealing a scenario marked by the weakening of public policies and the pedagogical control exerted by digital platforms such as RCO+Aulas. We discuss how initiatives aimed at cultural mediation and access to art in museum spaces often remain limited to superficial inclusion strategies, disconnected from meaningful aesthetic education. We argue that, for heritage education to fulfill its emancipatory role, it is essential to ensure adequate material conditions, pedagogical autonomy for teachers, and public policies committed to the right to culture and aesthetic experience within and beyond the school environment.